Decreased cerebral blood flow in the primary motor cortex in major depressive disorder with psychomotor retardation - Yin, Yingying; Wang, Meijian; Wang, Ze; Xie, Chunming; Zhang, Haisan; Zhang, Hongxing; Zhang, Zhijun; Yuan, Yonggui (Progress in neuro-psychopharmacology & biological psychiatry, 2018)
Psychomotor retardation (PMR) is one of the core symptoms of major depressive disorder (MDD) and has a specific pathophysiology, but studies of PMR remains sparse. The purpose of this study was to explore the cerebral blood flow (CBF) of PMR in MDD. One-hundred-seven antidepressant-free MDD patients and 48 normal controls (NCs) were recruited for this study. All subjects underwent arterial spin labeling-magnetic resonance imaging (ASL-MRI) for the CBF calculation. MDD patients were divided into the PMR group (N=35) and NPMR (non-PMR) group (N=72) according to the Salpetriere Retardation Rating Scale (SRRS) score. After a baseline MRI scan, patients began to receive antidepressant treatment. Thirty-nine patients (15 PMR, 24 NPMR) who were remitted after 8weeks participated in the follow-up MRI scan. For statistical analysis, subjects with unqualified MRI image and unmatched demographic data were ruled out. Consequently, 30 NCs and 60 patients (30 PMR, 30 NPMR) at baseline as well as 22 patients (11 PMR, 11 NPMR) at follow-up underwent statistical analysis. The PMR group showed significantly decreased CBF in the right primary motor cortex (PMC) at baseline, and the CBF value of the right PMC was significantly correlated with the SRRS score, whereas the CBF of the right PMC was increased in the PMR group at follow-up compared with the baseline in longitudinal comparison. Our findings suggest that the CBF of the right PMC is a potential biomarker of PMR in MDD. •This study focused on an important phenotype of major depressive disorder, psychomotor retardation.•We got findings from both cross and longitudinal section.•Our results consistently focused on the right primary motor cortex.